Up-conversion luminescence properties and temperature sensitivity of AgBi(MoO4)2:Yb3+/Er3+/Ho3+/Tm3+ phosphors. Issue 34 (10th August 2022) - Wu, Heyan; Liang, Yunhao; Ma, Yue; Yang, Jun; Hu, Shanshan
Abstract : A series of AgBi(MoO4 )2 :Ln 3+ luminous phosphors emitting green, yellow, blue and white light were obtained. And the AgBi(MoO4 )2 :Yb 3+ /Er 3+ phosphors show good temperature sensitivity with an absolute sensitivity maximum value of 1.32% K −1 at 463 K. Abstract : This work begins with a study of the synthesis of multi-color luminescence phosphors, which is followed by a discussion of the temperature sensitivity of AgBi(MoO4 )2 :Yb 3+ /Er 3+ . Uniform and approximately spherical particles of AgBi(MoO4 )2 -based phosphors were prepared by a simple one-step hydrothermal method without adding any surfactant. We obtained a series of rich green, yellow, blue, and white luminescence phosphors by doping Ln 3+ (Ln 3+ = Yb 3+, Er 3+, Ho 3+, Tm 3+ ) into the AgBi(MoO4 )2 matrix, and an analysis of various correlative factors was made, especially for the amounts of doping ions. Furthermore, the investigation of the temperature sensitivity of AgBi(MoO4 )2 :Yb 3+ /Er 3+ revealed that the fluorescence intensity becomes lower with increasing temperature from 323 to 573 K. The fluorescence intensity ratio (FIR) of the two thermal coupling energy levels ( 2 H11/2, 4 S3/2 ) of Er 3+ was calculated, and the absolute sensitivity of the obtained phosphor reached a maximum value of 1.32% K −1 at 463 K, as obtained by fitting the FIR as a function of temperature, which is a relatively high level compared with other related materials. This material is expected to be used as a highly sensitive FIR thermometer.